Characteristics of patients with mood disorders and schizophrenia who attempt suicide: a 15-year cross-sectional study in Japan - Kohei Harada; Nobuaki Eto; Leo Gotoh; Masato Masuda; Masahiro Ishida; Yuta Okamoto; Hikaru Hori (Academia Mental Health & Well-Being)
Introduction: Psychiatric disorders are an important risk factor for suicide. The aim of this study was to compare the characteristics of suicide attempts between patients with schizophrenia and mood disorders in Japan. Methods: From 596 patients treated after a suicide attempt in the Emergency and Critical Care Center (ECCC), during a 15-year period (2006 and 2021), two groups of patients were separated, 196 patients with mood disorders (21% bipolar mood disorder and 79% monopolar depression) and 112 patients with schizophrenia, who were compared according to sex, age, method of suicide attempt, and history of psychiatric treatment. We conducted multivariable logistic regression on the schizophrenia group and the mood disorder group, using those diagnoses as the dependent variable and age, suicide attempt method, sex, and history of psychiatric treatment as explanatory variables. Results: Patients with schizophrenia are significantly younger (39.4 ± 13.3 vs. 47.8 ± 17.9; p < 0.001) and significantly more frequently (89.3% vs. 64.3%; p < 0.001) had a history of psychiatric treatment than patients with mood disorders. Violent suicide methods were significantly more often used in the group of patients with schizophrenia (65.2% vs. 50.5%; p = 0.017) than in the group of patients with mood disorders. Jumping from a height was significantly more frequent in the group of patients with schizophrenia (36.6% vs. 16.8%; p < 0.001) than in the group of patients with mood disorders, while hanging was significantly more frequent in the group of patients with mood disorders (12.8% vs. 2.7%; p = 0.003) than in the group of patients with schizophrenia. As a result of multivariable logistic regression, the history of psychiatric treatment (OR = 0.25; 95%CI: 0.11–0.54; p < 0.001) was associated with high odds of the diagnosis of schizophrenia, while the use of the hanging method (OR = 7.25; 95%CI: 1.48–43.6; p = 0.014) was associated with high odds of the diagnosis of mood disorder. Conclusions: Patients with schizophrenia and mood disorders are groups with a high risk of suicidal behavior. Suicide prevention measures should consist of the urgent need for screening and evaluation of mental disorders by primary health care services, as well as successful treatment, successful follow-up of patients after hospitalization, improvement of adherence to therapy, and monitoring of risk factors.